Between spilling over and boiling down: network-mediated spillovers, absorptive capacity and productivity in European regions - Nicola Cortinovis; Frank van Oort (Tinbergen Institute, 2017)
Productivity across European regions is related to three types of networks that mediate R&D-related knowledge spillovers: trade, co-patenting and geographical proximity. Both our panel and instrumental variable estimations for European regions suggest that network relations are crucial sources of R&D spillovers, but with potentially different features. While co-patenting relations appear to affect local productivity directly, regions that link up to innovative leader regions via imports gain in productivity only when they have relatively high levels of human capital and absorptive capacity. From a policy perspective, this may frustrate recent European policy initiatives, such as Smart Specialization, that are designed to benefit all regions in Europe.
Keywords: R11; R12; O33; O47; 330; productivity; economic networks; regions; Europe; trade; knowledge